Myroides indicus sp nov., isolated from garden soil - Ram, Hari; Kumar, Alok; Thomas, Lebin; Dastager, Syed Gulam; Mawlankar, Rahul R.; Singh, Ved Pal (International Journal of Systematic and Evolutionary Microbiology, 2015)
A novel aerobic, non-motile, rod-shaped, catalase-and oxidase-positive bacterial strain, designated UKS3(T), was isolated from garden soil, and subjected to polyphasic taxonomic analysis. Strain UKS3(T) formed whitish, viscous colonies on nutrient agar and was Gram-staining negative. Phylogenetic analysis, based on 16S rRNA gene sequence, showed that maximum pairwise similarity occurs with representatives of the genus Myroides. The most closely related species include Myroides marinus JS-08(T) (92.7 % sequence similarity), Myroides phaeus MY15(T) (92.7 %), Myroides odoratus DSM 2801(T) (91.5 %) and Myroides odoratimimus CCUG 39352(T) (91.4 %). Strain UKS3(T) contained menaquinone-6 (MK-6) as the major respiratory quinone and iso-C-15 : 0 (40.2 %), anteiso-C-15 : 0 (9.4 %) and iso-C-17 : 0 3-OH (8.5 %) as major fatty acids. Phosphatidylethanolamine, phospholipids and three aminolipids were the major polar lipids. The DNA G + C content of strain UKS3(T) was 36.8 +/- 2.0 mol%. On the basis of phenotypic, chemotaxonomic and molecular analysis, strain UKS3(T) represents a novel species of the genus Myroides, for which the name Myroides indicus sp. nov., is proposed. The type strain is UKS3(T) (= DSM 28213(T) = NCIM 5555(T)).

Novel fatty alkene from marine bacteria: a thermo stable biosurfactant and its applications - Ram, Hari; Sahu, Amit Kumar; Said, Madhukar S.; Banpurkar, Arun G.; Gajbhiye, Jayant M.; Dastager, Syed G. (Journal of Hazardous Materials, 2019)
In this study, a novel thermo stable biosurfactants, 1-Pentanonacontene (C95H190) a fatty alkene and 3-Hydroxy16-methylheptadecanoic acid (C18H36O3) were isolated from a marine isolate SGD-AC-13. Biosurfactants were produced using 1% yeast extract in tap water as production medium at 24 h in flask and 12 h in bioreactor. Using 16S rRNA gene sequence (1515 bp) and BCL card (bioMerieux VITEK (R)), strain was identified as Bacillus sp. Crude biosurfactant reduced the surface tension of distilled water to 31.32 +/- 0.93 mN/m with CMC value of 0.3 mg/ml. Cell free supernatant showed excellent emulsification and oil displacement activity with stability up to 160 degrees C, pH 6-12 and 50 g/L NaCl conc. Biosurfactants were characterized using FTIR, TLC, HPLC LC-MS and NMR spectroscopy. Cell free supernatant reduced the contact angle of distilled water droplet from 117 degrees to 52.28 degrees and of 2% pesticide from 78.77 degrees to 73.42 degrees while 750 mu g/ml of crude biosurfactant reduced from 66.06 degrees to 56.33 degrees for 2% pesticide and recovered 35% ULO and 12% HWCO from the contaminated sand. To our best of knowledge, this is the first report of thermo stable fatty alkene as a biosurfactant and is structurally different from previously reported, with having potential application in agriculture, oil recovery and bioremediation.
Keywords: Bioremediation; Biosurfactants; Fatty alkene; Thermo stability; Wettability

Re-purposing is needed for beneficial bugs, not for the drugs - Ram, Hari; Dastager, Syed G. (International Microbiology, 2019)
Between 150 and 200 species of plants, insects, birds or mammals go extinct every day. We do not have any idea what the global extinction rate for microorganisms is. What is clear is that we have already lost a maximum number of the microbes that used to live in and on our skins. Many of our microbial partners are facing extinction as we apply selection pressures that are unprecedented in our long-standing relationships. Recent estimates are that we have lost at least one third of the diversity of our skin microbiome. Every day, most of us bath or shower in water that contains chlorine or fluorine; these additives do a great job of killing pathogenic microbes, but they are probably not helping our skin microbiome. Most of the people apply cosmetic products every day, as these products contain preservatives that prevent microbial growth on the shelf. These same chemicals may well kill microbes on the skin. The daily use of high-pH soaps probably will not help microbial life that is adapted to living on the skin's natural pH of 5. The rise in the rate of C-section births from around 5% in 1970 to more than 30% today is likely to be a contributing factor. Vaginal microbes seed our skins at birth and C-sections disrupt this process. The overuse of broad-spectrum antibiotics has contributed to the loss of our microbial partners in all body sites and the skin is no exception. It is now clear that skin is an ecosystem that is dependent on commensal microbes for optimal health. In general, a diverse ecosystem is a healthy ecosystem that is robust in the face of change. Low-diversity ecosystems are more fragile and susceptible to dysbiosis. Eczema and acne rates have increased rapidly over the last 50 years. These diseases are almost unknown in hunter-gatherer communities. Now, we face two exciting challenges: finding out which species matter and how to get them back.
Keywords: Drugs; Dysbiosis; Microbiome; Probiotics

Priestia veravalensis sp. nov., isolated from coastal sample - Wagh, Vasudev S.; Ram, Hari; Dastager, Syed G. (Archives of Microbiology, 2021)
The taxonomic position of two isolates, SGD-V-76(T) and SGD-M-37, isolated from sediment sample of Veraval coast, India, was examined using the polyphasic taxonomic approach. The morphological and chemotaxonomic characteristics of these two organisms are typical of the genus Priestia. The phylogenetic analyses performed using almost complete 16S rRNA gene sequences demonstrated that the isolate belongs to the Bacillaceae family, and forms a clade within the cluster containing Priestia flexus MTCC 2909(T), Priestia aryabhattai B8W22(T) and Priestia megaterium KCTC 3007(T) and both strains showed highest similarity of > 98% with 3-29 nucleotide differences. The cell wall contained meso-diaminopimelic acid as the diagnostic diamino acid. The predominant isoprenoid quinone was MK-7 and the G + C content of strains was 37.5-37.7 mol%. However, the DNA-DNA hybridization and the phenotypic characteristics revealed that, the strain SGD-V-76(T) and strain SGD-M-37 are similar species but different from any known Priestia species with ANI values of 79.2, 79.3 and 79.2 and the dDDH values of 17.7, 17.8 and 18.0% respectively. On the basis of phenotypic characteristics, phylogenetic analysis and the results of biochemical and physiological tests, and genomic data strain SGD-V-76(T) was clearly distinguished from closely related members of the Priestia genus. Based on the above data analysis strain SGD-V-76(T) (= DSM28242(T) = KCTC33802(T) = CIP111056(T) = NCIM5510(T)) represents a novel species of the genus Priestia, and we propose the name Priestia veravalensis sp. nov.
Keywords: Coastal sediment; genome; Priestia; Veraval

Multipurpose cellulases of Promicromonospora sp. VP111, with broad substrate specificity and tolerance properties - Thomas, Lebin; Ram, Hari; Singh, Ved P. (Journal of Basic Microbiology, 2023)
Cellulolytic actinobacterium, Promicromonospora sp. VP111 concomitantly produced cellulases (CELs), xylanase and pectinase when grown on commercial cellulose and untreated agricultural lignocellulosic residues (wheat straw and sugarcane bagasse). Secreted CELs hydrolyzed (enhanced with Co2+ ion) multiple cellulosic substrates, including sodium carboxymethyl cellulose (Na-CMC), Whatman filter paper no. 1, microcrystalline cellulose (avicel), p-nitrophenyl-beta-D-glucopyranoside (pNPG), laminarin, and cellulose powder. The CELs showed stabilities in the presence of various chemicals, including glucose (0.2 M), detergents (1%, w/v or v/v), denaturants (1%, w/v or v/v), and sodium chloride (NaCl, 30%, w/v). The CELs were fractionated using ammonium sulfate precipitation and dialysis. Activities (%) of fractionated CELs were retained at 60 degrees C for endoglucanase/carboxymethyl cellulase (CMCase) (88.38), filter paper cellulase (FPase) (77.55), and beta-glucosidase (90.52), which indicated of thermo-stability. Similarly, the activities (%) for CMCase (85.79), FPase (82.48), and beta-glucosidase (85.92) at pH 8.5 indicated of alkaline-stability. Kinetic factors, K-m and V-max for endoglucanase component of fractionated CELs were 0.014 g/l and 158.23 mu M glucose/min/mL, respectively. Fractionated CELs yielded activation energies (kJ/mol) of 17.933, 6.294, and 4.207 for CMCase, FPase, and beta-glucosidase activities, respectively in linear thermostable Arrhenius plots. Thus, this study reports on the multipurpose CELs from an untreated agricultural residue utilizing Promicromonospora in relation to broad substrate specificity, halo-tolerance, alkaline-tolerance, detergent-tolerance, thermo-tolerance, organic solvent-tolerance, and end product-tolerance.
Keywords: cellulases; cellulose; Endoglucanase; Lignocellulose; Promicromonospora sp; VP111